Population Pharmacokinetic/Pharmacodynamic Model-Guided Dosing Optimization of a Novel Sedative HR7056 in Chinese Healthy Subjects - Zhou, Ying; Hu, Pei; Huang, Yuguang; Sang, Nuoer; Song, Kaicheng; Wang, Hongyun; Wen, Jinhua; Jiang, Ji; Chen, Xia (Frontiers in Pharmacology, 2018)
HR7056 is a new benzodiazepine, showing more faster acting onset and recovery than currently available short-acting sedatives. To avoid inadequate anesthesia and predict return of cognition, allowing for immediate neurological evaluation, HR7056 pharmacokinetics and pharmacodynamics were characterized in Chinese healthy subjects. We report on modeling of the data and simulations of dosage regimens for future study. Up to 63 subjects were evaluated, using Bispectral Index (BIS) and Modified Observer’s Assessment of Alertness/Sedation (MOAA/S) as pharmacodynamics endpoints. A three-compartment model best described HR7056 pharmacokinetics. Total clearance was 1.49 L min-1, central volume was 2.1 L, inter-compartmental clearances were 0.96 L min-1 and 0.27 L min-1, respectively. The population mean pharmacodynamic parameters were as follows: BIS, E0: 95.3; IC50: 503 ng mL-1; γ: 1.5; ke0: 0.0855 min-1; Imax: 47.9 and MOAA/S, IC50: 436 ng mL-1; γ: 1.5; ke0: 0.05 min-1; Imax: 27.9. The model simulation will enable maintenance doses to be given more accurately for future study (Clinical trial registration: NCT01970072).